Observation of the Λb0→Λ+cK+K−π− decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2021)
The Λb0→Λc+K+K−π− decay is observed for the first time using a data sample of proton-proton collisions at centre-of-mass energies of s=7 and 8TeV collected by the LHCb detector, corresponding to an integrated luminosity of 3fb−1. The ratio of branching fractions between the Λb0→Λc+K+K−π− and the Λb0→Λc+Ds− decays is measured to beB(Λb0→Λc+K+K−π−)B(Λb0→Λc+Ds−)=(9.26±0.29±0.46±0.26)×10−2, where the first uncertainty is statistical, the second systematic and the third is due to the knowledge of the Ds−→K+K−π− branching fraction. No structure on the invariant mass distribution of the Λc+K+ system is found, consistent with no open-charm pentaquark signature.
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D, Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, A. Piucci, M. Schmelling, S. Stemmle, D.J. Unverzagt. U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 30.06.2021
Im Titel sind "0", Plus- und Minuszeichen hochgestellt, "b" und "c" tiefgestellt